The Effect of TPF, NPF and Fee Based Income on the Profitability of Islamic Banks with Financing as an Intervening Variable - Ridwan Ridwan; Sugianto Sugianto; Eka Setyawati (Budapest International Research and Critics University, 2021)
The purpose of this study was to examine the effect of DPK, NPF, and Fee Based Income on the Profitability of Syari'ah Banks with financing as an intervening variable. This study uses secondary data from the 2010-2019 period in Islamic banks. The sampling technique used purposive sampling. Tools for processing data using SPSS 20.0. The results showed that DPK had a direct insignificant effect on the profitability variable, while DPK had a significant direct effect on the financing variable. Furthermore, DPK indirectly does not have a significant effect on profitability through financing. And the financing variable cannot mediate the effect of the DPK variable on profitability. NPF directly has a negative and significant effect on NPF Profitability, directly there is an insignificant effect on the financing variable. NPF indirectly has a significant effect on profitability through financing. And the financing variable can mediate the effect of the NPF variable on profitability. Fee Based Income has a negative and significant effect directly on profitability. The direct financing variable does not have a significant effect on profitability.